2013
DOI: 10.1186/1471-2334-13-419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Giardia duodenalis and Cryptosporidium species infections among children and cattle in North Shewa Zone, Ethiopia

Abstract: BackgroundGiardia and Cryptosporidium are the most common causes of protozoan diarrhea that lead to significant morbidity and mortality worldwide. The purpose of this study was to determine the prevalence of Giardia duodenalis and Cryptosporidium species infections among children and cattle, and to assess the potential risk of zoonotic transmission.MethodsThis cross-sectional study was conducted between January and April 2009 in Girar Jarso and Dera Districts of North Shewa Zone, Oromia Region, Ethiopia. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
56
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 18 publications
18
56
7
Order By: Relevance
“…The infection rate across regions ranged from 21.87% to 40.74%. This result agreed with results obtained by Wegayehu et al (2013). The infection rate of males (24.24%) and females (38.18%) of Cryptosporidium spp.…”
Section: February 2016 | Volume 4 | Issue 2 | Page 52supporting
confidence: 83%
See 1 more Smart Citation
“…The infection rate across regions ranged from 21.87% to 40.74%. This result agreed with results obtained by Wegayehu et al (2013). The infection rate of males (24.24%) and females (38.18%) of Cryptosporidium spp.…”
Section: February 2016 | Volume 4 | Issue 2 | Page 52supporting
confidence: 83%
“…In regards with the prevalence of Cryptosporidium spp. in breeders of cattle the estimation ranged between 8.5% -37.50% (Byomi et al, 2010;Naguib et al, 2013;Wegayehu et al, 2013). The objective of this study was to identify the relation between the prevalence of Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Immunocardstat Crypto/ Giardia was not already evaluated in non diarrheic patients. Cysts and vegetative forms were detected in 18.5 % of children, confirming the existence of a non-negligible human reservoir of G. duodenalis among adults and children, as described elsewhere (Ouattara et al 2008;Wegayehu et al 2013). Moreover, at the Plaine-Orety district of Gabon, the proportion of children with C. spp.…”
Section: Discussionsupporting
confidence: 50%
“…Although Cryptosporidium and Giardia infections have been reported for cattle in many parts of the world, prevalence data have often varied markedly. The present detection rate of Cryptosporidium infection based on microscopic examination is much higher compared to the obtained prevalence in former studies in Thailand, Argentina, Ethiopia, England, India and Wales with the prevalence of 0.6, 19.35, 7.8, 12.50 and 10.2 per cent, respectively (Jittapalapong et al, 2006;Tiranti et al, 2011;Wegayehu et al, 2013;Singla et al, 2013;Smith et al, 2014). Similar results with this study, high prevalence rates were also reported in Canada, Germany, Nigeria, Tanzania and Brazil with the prevalence rates of 32, 41.3, 33.0, 35 and 45 per cent, respectively (Budu-Amoako et al, 2012;Gillhuber et al, 2014;Faleke et al, 2014;Swai and Schoonman, 2010;Almeida et al, 2010).…”
Section: Resultsmentioning
confidence: 54%